Dengue virus circulation and evolution in Mexico: a phylogenetic perspective (2006)
ABSTRACT: Background: Dengue is the most important arthropod-borne viral infection in the Americas. In the last decades a progressive increment in dengue severity has been observed in Mexico and other countries of the region. Methods: Molecular epidemiological studies were conducted to investigate the viral determinants of the emergence of epidemic dengue, dengue hemorrhagic fever and dengue shock syndrome as major public health problems in Mexico. Bayesian phylogenetic analyses were conducted to determine the origin, persistence and geographical dispersion of the four serotypes of dengue virus (DENV) isolated in Mexico between 1980 and 2002. Tests for natural selection were also conducted. Results: The origin of some, but not all, strains circulating in Mexico could be inferred. Frequent lineage replacements were observed and were likely due to stochastic events. In situ evolution was detected but not associated with natural selection. Recent changes in the incidence and severity of dengue were temporally associated with the introduction and circulation of different serotypes and genotypes of DENV. Conclusions: Introduction of new DENV genotypes and serotypes is a major risk factor for epidemic dengue and severe disease. Increased surveillance for such introductions is critical to allow public health authorities to intervene in impending epidemics.